Glossophobia: A Cross-Sectional Assessment of Public Speaking Anxiety among Saudi Nursing Students - Deena Faisal Rayani; AlBatool Mohammed Bin Sallman; Reem Mohammed Barayan; Raghad Ahmed Maghrabi; Nahed Mohamed Morsy; Hala Ahmed Elsayes; Alaa Nabil Mahsoon; Loujain Saud Sharif (Nurse Media: Journal of Nursing)
Background: Public speaking anxiety or glossophobia is common among college students, especially those studying in their non-primary language. Effective public speaking is considered an essential skill for nursing students to grasp as their future roles require it as patient advocates. Little is known about the effects of glossophobia amongst Arab students studying nursing in a second language (English).